Writing and Reporting News. A Coaching Method - Rich, Carole (Belmont Thomson Wadsworth, 2005)
Writing and Reporting News: A Coaching Method, Media Enhanced Fourth Edition will teach you the fundamental skills required of a successful journalist from conceiving and researching to organizing and writing news. Youll learn writing basics and journalism ethics and be ready to write effectively for any news medium.
Keywords: Writing